Human Chondrocytes from Human Adipose Tissue-Derived Mesenchymal Stem Cells Seeded on a Dermal-Derived Collagen Matrix Sheet: Our Preliminary Results for a Ready to Go Biotechnological Cartilage Graft in Clinical Practice. (24th February 2021) - Dang, Quan Tran; Huynh, Thao Duy; Inchingolo, Francesco; Dipalma, Gianna; Inchingolo, Alessio Danilo; Cantore, Stefania; Paduanelli, Gregorio; Nguyen, Kieu Cao Diem; Ballini, Andrea; Isacco, Ciro Gargiulo; Tran, Cong Toai
Abstract : Background . The articular cartilage is unique in that it contains only a single type of cell and shows poor ability for spontaneous healing. Cartilage tissue engineering which uses mesenchymal stem cells (MSCs) and adipose tissue-derived mesenchymal stem cells (AT-MSCs) is considered an attractive treatment for cartilage lesions and osteoarthritis. The establishment of cartilage regenerative medicine is an important clinical issue, but the search for cell sources able to restore cartilage integrity proves to be challenging. The aim of this study was to create cartilage grafts from the combination of AT-MSCs and collagen substrates. Methods . Mesenchymal stem cells were obtained from human donors' adipose tissue, and collagen scaffold, obtained from human skin and cleaned from blood vessels, adipose tissues, and debris, which only preserve dermis and epidermis, were seeded and cultured on collagen substrates and differentiated to chondrocytes. The obtained chondrocyte extracellular matrix of cartilage was then evaluated for the expression of chondrocyte-/cartilage-specific markers, the Cartilage Oligomeric Matrix Protein (COMP), collagen X, alpha-1 polypeptide (COL10A1), and the Collagen II, Human Tagged ORF Clone (COL2A1) by using the reverse transcription polymerase chain reaction (RT-PCR). Results . Our findings have shown that the dermal collagen may exert important effects on the quality of in vitro expanded chondrocytes, leading in this way that the influence of collagen skin matrix helps to produce highly active and functional chondrocytes for long-term cartilage tissue regeneration. Conclusion . This research opens up the possibility of generating cartilage grafts with the precise purpose of improving the existing limitation in current clinical procedures.